Tracing the paths: a systematic review of mediators of complex trauma and complex post-traumatic stress disorder - Harris, Joseph; Loth, Eva; Sethna, Vaheshta (Frontiers in Psychiatry, 2024)
Complex trauma is associated with complex-posttraumatic stress disorder (CPTSD). While dissociative processes, developmental factors and systemic factors are implicated in the development of CPTSD, there are no existing systematic reviews examining the underlying pathways linking complex trauma and CPTSD. This study aims to systematically review evidence of mediating factors linking complex trauma exposure in childhood (birth to eighteen years of age) and subsequent development of CPTSD (via self-reports and diagnostic assessments). All clinical, at-risk and community-sampled articles on three online databases (PsycINFO, MedLine and Embase) were systematically searched, along with grey literature from ProQuest. Fifteen articles were eligible for inclusion according to pre-determined eligibility criteria and a search strategy. Five categories of mediating processes were identified: 1) dissociative processes; 2) relationship with self; 3) emotional developmental processes; 4) social developmental processes; and 5) systemic and contextual factors. Further research is required to examine the extent to which targeting these mediators may act as mechanisms for change in supporting individuals to heal from complex trauma.